Peningkatan Pemahaman Konsep Cahaya Melalui Kegiatan Praktikum Berbasis Media Bahan Bekas Pakai - Nining Sariyyah; Margaretha Dua Lado (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
The purpose of this study was to determine the increase in mastery of the concept of light after the use of used material-based media in fifth grade students of SDI Key, Nita Subdistrict, Sikka District. The type of research used was classroom action research. The subjects in this study were the 14th grade SDI Key students. Data taken in the form of observation, tests, interviews, and documentation. The data analysis technique is qualitative. The results show that there is an increase in mastery of the concept of light in the context of light can propagate straight, light can penetrate clear objects, light can be reflected, light can be refracted and light can be decomposed from 64.28% to 100% from cycle I to cycle II.